Effective oral favipiravir (T-705) therapy initiated after the onset of clinical disease in a model of arenavirus hemorrhagic Fever. - Michelle Mendenhall; Andrew Russell; Donald F Smee; Jeffery O Hall; Ramona Skirpstunas; Yousuke Furuta; Brian B Gowen (Public Library of Science (PLoS), 2011)
Lassa and Junín viruses are the most prominent members of the Arenaviridae family of viruses that cause viral hemorrhagic fever syndromes Lassa fever and Argentine hemorrhagic fever, respectively. At present, ribavirin is the only antiviral drug indicated for use in treatment of these diseases, but because of its limited efficacy in advanced cases of disease and its toxicity, safer and more effective antivirals are needed.Here, we used a model of acute arenaviral infection in outbred guinea pigs based on challenge with an adapted strain of Pichindé virus (PICV) to further preclinical development of T-705 (Favipiravir), a promising broad-spectrum inhibitor of RNA virus infections. The guinea pig-adapted passage 19 PICV was uniformly lethal with an LD(50) of ∼5 plaque-forming units and disease was associated with fever, weight loss, thrombocytopenia, coagulation defects, increases in serum aspartate aminotransferase (AST) concentrations, and pantropic viral infection. Favipiravir (300 mg/kg/day, twice daily orally for 14 days) was highly effective, as all animals recovered fully from PICV-induced disease even when therapy was initiated one week after virus challenge when animals were already significantly ill with marked fevers and thrombocytopenia. Antiviral activity and reduced disease severity was evidenced by dramatic reductions in peak serum virus titers and AST concentrations in favipiravir-treated animals. Moreover, a sharp decrease in body temperature was observed shortly after the start of treatment. Oral ribavirin was also evaluated, and although effective, the slower rate of recovery may be a sign of the drug's known toxicity.Our findings support further development of favipiravir for the treatment of severe arenaviral infections. The optimization of the experimental favipiravir treatment regimen in the PICV guinea pig model will inform critical future studies in the same species based on challenge with highly pathogenic arenaviruses such as Lassa and Junín.